2017
DOI: 10.1038/ncomms14173
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal crystals with diamond symmetry at optical lengthscales

Abstract: Future optical materials promise to do for photonics what semiconductors did for electronics, but the challenge has long been in creating the structure they require—a regular, three-dimensional array of transparent microspheres arranged like the atoms in a diamond crystal. Here we demonstrate a simple approach for spontaneously growing double-diamond (or B32) crystals that contain a suitable diamond structure, using DNA to direct the self-assembly process. While diamond symmetry crystals have been grown from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 42 publications
0
87
0
Order By: Relevance
“…Still, rigorous resolution to these questions will require additional work. Studies in µ-sized colloidal self-assembly [43], including DNA [44,45], where according to the OTM [18] particles cannot display non-hard sphere behaviour, may provide even better models to investigate the tendency towards icosahedral order than the NCs discussed in this study, as some phases with f ico = 0 become suppressed. SC REGIME SC REGIME ICOSAHEDRAL REGIME …”
mentioning
confidence: 99%
“…Still, rigorous resolution to these questions will require additional work. Studies in µ-sized colloidal self-assembly [43], including DNA [44,45], where according to the OTM [18] particles cannot display non-hard sphere behaviour, may provide even better models to investigate the tendency towards icosahedral order than the NCs discussed in this study, as some phases with f ico = 0 become suppressed. SC REGIME SC REGIME ICOSAHEDRAL REGIME …”
mentioning
confidence: 99%
“…PAEs have been synthesized on both the nanoscale (2–1000 nm) and microscale with the same basic DNA design, and all follow the same design rules as particles in the ≈10–50 nm core size regime (Figure ). The key rule that governs the crystallization of different PAE sizes is that the overall hydrodynamic radius of the PAE determines its binding behavior, not the core size alone .…”
Section: Versatility In the Pae Constructmentioning
confidence: 99%
“…While the predominant driving force that dictated the thermodynamically favorable lattice structure for a given set of PAEs was initially discovered to be almost entirely an enthalpic maximization of DNA binding, it was later found that entropic effects could be increased with flexible DNA linkers, thereby inducing self‐complementary PAEs to form a bcc lattice even though this structure represents a lower packing density than the prior fcc structures that had been obtained in unary systems . Making the core–core interactions appreciable in scale, one study created the binary phase isostructural to sodium‐thallium (NaTl) . Additionally, it was discovered that higher energy unit cells could be synthesized in a kinetically trapped state under the correct conditions (e.g., hexagonal close packed (hcp) lattices form as a kinetic structure for PAEs whose thermodynamically preferred phase is fcc) .…”
Section: Versatility In the Pae Constructmentioning
confidence: 99%
“…This structure can also be viewed as Double Diamond (DD) lattices, which enables its conversion to a regular diamond through partial particle deletion. Interestingly, self-assembly of DD lattice has been recently observed in conventional (non-patch) colloidal system with DNA-mediated interaction, but the mechanism behind its formation remains obscure [26].…”
Section: Introductionmentioning
confidence: 99%